FRI0481 Giant cell arteritis and inflammatory bowel disease – is there a connexion? results from a population-based study. (12th June 2018) - Yavne, Y.; Tiosano, S.; Watad, A.; Comaneshter, D.; Cohen, A.D.; Amital, H.
Abstract : Background: Giant cell arteritis (GCA) is an autoimmune disorder which primarily affects large vessels, whilst inflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC), mainly targets the gut. Co-existence of the two maladies has been reported sporadically in the literature 1–3 . Objectives: The purpose of this study was to assess the authenticity of such an association in a large, cross-sectional study. Methods: Utilising data derived from the Clalit Health Services' registry, the largest health maintenance organisation in Israel, we compared the proportion of CD and UC in GCA patients with age- and gender-matched controls. Univariate analysis was performed using Chi-square and student t -test and a multivariate analysis was performed using a logistic regression model. Results: The study included 5, 657 GCA patients and 28 298 age- and gender-matched controls. GCA patients had a significantly increased proportion of both CD and UC in comparison with controls (0.81% vs. 0.12% and 0.69% vs. 0.2%, p-value <0.001, respectively). The strength of the association between GCA and IBD was negatively correlated with the patients' age; thus the association was most robust amongst younger patients aged 18–44 (OR=13.2, figure 1). The association between GCA and IBD remained significant when evaluated independently of confounding factors (OR=2.367, p-value <0.001, table 1). Conclusions: The probability that GCA patients may also suffer from IBD is increased in comparison with age- and gender-matched controls. Our findings indicate that this association is most prominent in younger patients (<70). Screening for IBD amongst GCA patients in this age group may be warranted. References: [1] Colombat M, et al. Giant cell arteritis localized to the colon associated with Crohn's disease. Histopathology2001;38(1):21–24. [2] Sy, Alice, et al. Vasculitis in patients with inflammatory bowel diseases: A study of 32 patients and systematic review of the literature. Seminars in arthritis and rheumatism2016;45(4);Elsevier. [3] Sanges, Sébastien, et al. Giant cell arteritis and ulcerative colitis: An unusual association. Seminars in arthritis and rheumatism2016;46(1)Elsevier. Disclosure of Interest: None declared